Posted by **Jake** on Thursday, January 26, 2012 at 7:15pm.

Explain how to do this with steps please.

1. Simplify cos(x-y)+cos(x+y)/cosx

Formula: cosxcosy= cos(x+y)+cos(x-y)/2

cos(x-y)+cos(x+y)/cosx

=cosxcosy/2cosx

## Answer This Question

## Related Questions

- Math - Explain how to do this with steps please. 1. Simplify cos(x-y)+cos(x+y)/...
- Trig - prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= ...
- pre-cal - Simplify the given expression........? (2sin2x)(cos6x) sin 2x and cos ...
- RESPONSE to PreCalc Question - h t t p : / / w w w . j i s k h a . c o m / d i s...
- Math, please help - Which of the following are trigonometric identities? (Can be...
- Math help again - cos(3π/4+x) + sin (3π/4 -x) = 0 = cos(3π/4)cosx...
- math - Determine exact value of cos(cos^-1(19 pi)). is this the cos (a+b)= cos a...
- calculus - Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x...
- Calc. - Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln...
- Calc II - For the following question, we need to find the length of the polar ...

More Related Questions